Regression Equation and Multiplication Factor for the Reconstruction of Stature by Femur Length - Karki, Raj Kumar; Singh, Pankaj Kumar; Khan, Abdul Sami; Regmi, Sudeep (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Stature is the important parameter along with age, sex and race while identifying bodies. Stature has direct relationship with the skeletal dimensions most importantly with lower limbs. This study attempts to derive regression equation (RE) and multiplication factor (MF) from femur length (FL) which could be used for stature reconstruction. MATERIAL AND METHODS The study was conducted amongst the 160 students and staff of Dhulikhel Hospital, Nepal for the period of six months from February 2020 to July 2020. The sample was composed of 95 males and 65 females between the age of 18 - 40 years. The femoral length and height was measured in standard position using standard measuring instruments. Statistical analysis was done using SPSS 25. RESULTS The mean height and femur length of overall sample was 162.33 ±7.62 cm and 40.14 ±2.132 cm respectively, male surpassing the female dimensions. There was a strong correlation between femur length and stature (r = 0.723, 0.869 and 0.791 for males, females, and overall participants respectively). MF was derived as 4.084 ±0.139, 3.99 ±0.11, 4.047 ±0.135 and RE was derived as y = 75.51 + 2.13*FL ±4.06, y = 55.238 + 2.581*FL ±2.999, y = 48.791 + 2.829*FL ±4.672 for males, females and overall participants. Both methods were checked for accuracy and could successfully interpret the height (p>0.05). CONCLUSION The femoral length was found to be a reliable estimator of stature of an individual by using both RE and MF.